A comparative study of the use of two technologies as a quality factor in quinoa (Chenopodium quinoa willd) processing - Arapa Carcasi, Percy (2019)
This article shows the results of the comparison of using a non-continuous system technology and a continuous system technology in terms of the quality obtained in both processes. The non-continuous system technology produces second class quinoa with a yield of 86 %, and the continuous system technology produces first class quinoa with a yield of 96 %, which represents a significant difference between both systems.